Relationship of sustainable economic development and environmental performance via moderating effect of governance in developing and developed countries - Tan, Chee Leong (2022)
Economic outcomes and expectations may differ between developing and developed countries, primarily due to different stages of economic development. Nonetheless, governments of developing and developed countries alike are focusing on sustainable economic development (SED) to ensure self-sufficiency in food, total employment, and financial stability without relying on foreign aid. To achieve these objectives, governments continue to exploit natural resources via unsustainable industrialisation, causing deforestation and air and water pollution, which ultimately destroys the natural ecosystem. Unfortunately, the general perception is that environmental conservation will not bring any commercial benefits. Instead, conservation relies on the government’s or institution’s budget to maintain the order of ecology and in return minimise environmental impacts. Though some empirical studies argue that corporate environmental efforts bring in good revenue through tourism spending, environmentally friendly industries, green-label industries, and environment-conscious investments, both developing and developed countries continue to emphasise economic development rather than environmental performance. Therefore, this study aimed to investigate the relationship of sustainable economic development (SED) and environmental performance (EP) via moderating effect of country governance (CG) in developing and developed countries. The underpinning theories adopted in this study were the Environmental Kuznets Curve (EKC), Ecological Modernisation Theory (EMT), Neoliberal Environmental Governance (NEG), and Great Moderation (GM). Past studies on the nexus between SED, EP, and CG have focused on the company or institution level. This study, in contrast, addressed the country level in terms of developing and developed countries. Data on SED was obtained from the World Bank and International Monetary Fund (IMF) database, which included Gross Domestic Product (GDP), Foreign Direct Investment (FDI), Net Capital Account (NCA), and Central Government Debt ratio to GDP (DEBT). EP was represented by the Environmental Performance Index (EPI), the data of which was developed by Yale University and Columbia University. CG was represented by Worldwide Governance Indicators (WGIs), whereby the data was produced by the Natural Resource Governance Institute (NRGI) and World Bank Institute. All data was obtained from an even number of years from 2006 to 2018. This study also took into consideration the control variables of primary school enrolment (SCH) and country population (POP), which may potentially influence the outcome of this study. A panel regression analysis based on the fixed effect model was performed to examine the nexus of SED, EP, and CG. Overall, the findings contribute to the economic literature by demonstrating the impact of the SED on EP in developing and developed countries. This study also confirms the effectiveness of CG for EP by preventing environmental degradation and enhancing environmental conservation. This study further proves the effectiveness of CG in moderating the link between SED and EP for optimised performance. The outcomes of this study provide a new perspective and recommend relevant strategies for improving the usage of a country's resources to achieve balanced performance among SED, EP, and CG. The findings further contribute to governments, institutions, and agencies as inputs to improve CG policies. Potential investors or fund managers can also use the findings as a guideline for making sound investment decisions. Finally, the study serves as a reference for academicians by providing informative knowledge and filling the gap in the existing economics and environmental literature.